Algorithm of Equivalent Inter-phase Impedance for Three-phase Unbalanced Loads and Its Applications - ZHU Mingxing; SUN He; GUAN Shenlong; HU Maoliang; JIAO Yadong (Kongzhi Yu Xinxi Jishu)
It presented a method for calculating equivalent inter-phase impedance of three-phase unbalanced loads in three-phase three-wire system. Phase voltages and line currents of unbalanced system were decomposed into positive sequence and negative sequence components by using symmetrical component method. Negative sequence current was rotated to be positive sequence by taking the minimum line current as references. Inter-phase current was acquired by the subtraction of negative sequence and positive sequence of the negative-sequence current. Sequence impedance and inter-phase impedance were calculated by voltage and current sequence components and then equivalent inter-phase impedance of unbalanced loads could be calculated. Simulink models were built to verify the correctness of the proposed arithmetic in two assumptive situations of single phase and three phase. Model of equivalent impedance and compensation network was established, and balancing compensation was applied in virtual three-phase unbalanced loads by using the balance compensation principle so as to reflect the applicability of the algorithm.